Application of IVIM-DWI in Detecting the Tumor Vasculogenic Mimicry Under Antiangiogenesis Combined With Oxaliplatin Treatment - Liang, Jianye; Li, Zhipeng; Li, Jing; Peng, Chuan; Dai, Wei; He, Haoqiang; Zeng, Sihui; Xie, Chuanmiao (Frontiers in Oncology, 2020)
Objectives: This study aimed to detect the time window of vascular normalization during anti-vascular treatment using intravoxel-incoherent-motion diffusion-weighed imaging (IVIM-DWI). Simultaneously, we evaluated the tumor invasiveness and vasculogenic mimicry, and performed synthetic assessment of treatment efficacy of angiogenesis inhibitor combined with conventional chemotherapy using IVIM-DWI. Materials and Methods: HCT116 cells were subcutaneously administrated into the right flank of BALB/C nude mice to build a colon cancer xenograft model. Thirty-two tumor-bearing mice were randomly divided into four groups and intraperitoneally administrated with normal saline (Group A or Control Group), bevacizumab (B), oxaliplatin monotherapy (C) and oxaliplatin combined with bevacizumab (D). The IVIM-DWI was performed on days 0, 3, 6, 9, 12 and 15 after the treatments. Another 51 tumor-bearing mice were included in the pathological examinations.α-SMA and CD31 double-staining, PAS and CD31 double-staining, HE, Ki-67, and E-cadherin staining were performed. The tumor growth and dynamic change of each parameter were noted. Results: The mice in Group D manifested the smallest tumor volume and highest tumor inhibition rate. Microvessel density was significantly decreased but accompanied by increased vasculogenic mimicry after anti-angiogenic treatment. The trend was reversed by oxaliplatin treatment. Treated with bevacizumab, the vessel maturity index shared a similar trend with D* and f values during day 3 to 12, which slowly increased from day 0 to day 9 and then decreased briefly. D value significantly correlated with vasculogenic mimicry and Ki-67, while D* and f values showed positive correlations with microvessel density and E-cadherin, an indicator of epithelial-mesenchymal transition. Conclusion: Oxaliplatin performed an inhibited effect on vasculogenic mimicry. Bevacizumab can enhance the tumor chemotherapy through vascular normalization within a transient time period, which can be detected by IVIM-DWI. D* and f values are able to predict the tumor invasiveness while D is superior in reflecting vasculogenic mimicry and Ki-67 expression during anti-tumor treatment.